Progress in the total synthesis of resin glycosides - Wang, Wenli; Li, Yuxin; He, Ye; Jiang, Xing; Yi, Ying; Zhang, Xihan; Zhang, Shiyu; Chen, Guangtong; Yang, Min; Luo, Jia-Lie; Fan, Boyi (Frontiers in Chemistry, 2022)
Resin glycosides, mainly distributed in plants of the family Convolvulaceae, are a class of novel and complex glycolipids. Their structural complexity and significant biological activities have received much attention from synthetic chemists, and a number of interesting resin glycosides have been synthesized. The synthesized resin glycosides and their analogues not only helped in structural verification, structural modification, and further biological activity exploration but also provided enlightenment for the synthesis of glycoside compounds. Herein, the present review summarizes the application of various efforts toward the synthesis of resin glycosides in the last decade.